The Concept of a Method for Predicting the Cascade Effect Under Conditions of Hybrid Warfare - WRÓBLEWSKI Wojciech; WIŚNIEWSKI Michał (Foundations of Management)
The changing nature of conflicts is creating new challenges in civilian protection. Features of hybrid warfare, such as multidimensionality, synergistic effects, blurring of boundaries, or asymmetricity, force practitioners and scholars to consider new threats. The article examines how the characteristics of hybrid warfare affect the emergence of cascade effects. We conducted research on examples of the war in Ukraine and the Israeli-Palestinian war. The concept of a method for predicting the cascade effect under conditions of hybrid war is proposed. The concept involves using the Six Ways to Die method to take areas affecting the health and life of the civilian population and define a network of object dependencies on which proper functioning of the State in these areas depends. Using complementary tools such as process analysis, risk assessment, Petri nets, and Bayesian network in the form of the Critical Infrastructure Security Situational Management methodology, the authors provide a comprehensive solution for modeling how to protect the life and health of the civilian population. To the author’s knowledge, this is the first holistic study in this issue.